Poster Session 3: Epidemiology 2018
DOI: 10.1136/lupus-2018-abstract.105
|View full text |Cite
|
Sign up to set email alerts
|

PS3:58 Lipid profile characterisation in patients with juvenile sle with and without lupus nephritis – experience of a portuguese centre

Abstract: sites and relation to clinical characteristics, laboratory features and disease activity. Patients and methods Medical records of 250 Egyptian SLE patients attending the Rheumatology department, Cairo University hospitals were reviewed retrospectively for the clinical and laboratory features, SLE disease activity index (SLEDAI) and treatment received. Results Infection was found in 119 (47.6%) patients, with bacterial infection being the commonest in 99 (83%) followed by fungal infection in 30 (25%) and viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…10 two-arm studies (n=1207) had the required data for analysing the relationship between LN and lipid profile. 4 24 25 27 32 35 37 38 41 43 Seven of them included the mean total TC levels, 24 25 35 37 38 41 43 while six included the mean HDL, LDL and TG levels. 24 25 35 37 41 43 Three studies reported the OR of hyperlipidaemia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 two-arm studies (n=1207) had the required data for analysing the relationship between LN and lipid profile. 4 24 25 27 32 35 37 38 41 43 Seven of them included the mean total TC levels, 24 25 35 37 38 41 43 while six included the mean HDL, LDL and TG levels. 24 25 35 37 41 43 Three studies reported the OR of hyperlipidaemia.…”
Section: Resultsmentioning
confidence: 99%
“…4 24 25 27 32 35 37 38 41 43 Seven of them included the mean total TC levels, 24 25 35 37 38 41 43 while six included the mean HDL, LDL and TG levels. 24 25 35 37 41 43 Three studies reported the OR of hyperlipidaemia. 4 27 32 The pooled outcomes showed that patients with SLE with LN were associated with significantly higher TC (MD=0.44, 95% CI=0.12 to 0.76, p=0.006, I 2 =73%) ( figure 3A ), LDL (MD=0.37, 95% CI=0.02 to 0.71, p =0.04, I 2 =70%) ( figure 3B ) and risk of hyperlipidaemia (OR=11.03, 95% CI=4.20 to 28.95, p<0.00001, I 2 =0%) ( figure 3E ) within the random-effects model.…”
Section: Resultsmentioning
confidence: 99%